A new species of Tapiena (Orthoptera: Tettigonioidea: Phaneropterinae) from Brunei Darussalam (Borneo, Southeast Asia) - Tan, Ming Kai; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2018)
There are now more than 28,000 described orthopterans globally (Cigliano et al., 2018) and this figure is likely to increase in the future. The same is true for Southeast Asia, where we are still at a stage of discovering species new to science, and this is partly an artefact of incomplete sampling (Tan et al., 2017a). In one of the most popular biodiversity hotspots, i.e., Borneo, is the Kuala Belalong Field Studies Centre. It is located in the primary lowland and ridge dipterocarp forests of the Ulu Temburong National Park, Brunei Darussalam. Recent collection of orthopterans in the area led to the discovery of several new species of katydids (Tan et al., 2017b; Tan & Wahab, 2017a) and crickets (Tan et al., 2017c; Tan & Wahab, 2017b). Here, we describe another new species of katydid, from the genus Tapiena Bolívar, 1906. Tapiena currently consists of 26 species (Tan et al., 2015) and is distributed around Asia and even Africa. In Borneo, only one species is known: Tapiena incisa Karny, 1923 from Sarawak (see Karny, 1923). The new species Tapiena paraincisa sp. nov. represents the second species described from Borneo.